A dual-channel fluorogenic probe for simultaneous and distinguishable imaging of protein monothiols and vicinal-dithiols in live cells. (April 2023) - Gao, Wei; Lu, Shuaimin; Zhang, Shilong; Liu, Junjie; Kang, Jin; Yin, Caixia
Abstract: Protein monothiols (MTs) and vicinal-dithiols (VDTs) are ubiquitous in living systems. Redox states of these protein thiols are mutually coupled and balanced, and their alterations are essential for regulating diverse biological processes in cells. However, there is still a lack of sensing strategies for simultaneous and distinguishable imaging of protein MTs and VDTs in live cells. Here, we report the design and synthesis of a fluorogenic probe bearing two thiol-reactive sites embedded into a viscosity/polarity-dual-sensitive fluorophore, which response to protein MTs and VDTs in two different fluorescence channels. This probe enables us to visualize and analyze protein MTs and protein VDTs in living cell without interference from the high abundant small biothiols such as glutathione. We believe that this work would inspire the development of other fluorogenic probes to protein thiols with more elaborated functions (e.g., targeting to subcellular organelles) and would benefit studies on redox signaling mechanism in live cells and other biological processes involving alteration of protein thiols. Graphical abstract: Image 1 Highlights: A fluorogenic probe bearing two thiol-reactive sites depending on viscosity/polarity was obtained. The probe can response to protein MTs and VDTs in two different fluorescence channels. This probe can analyze protein MTs and protein VDTs in living with high selectivity.